Examining the Relationship Between Incentives, Workload, and Employee Performance: A Systematic Literature Review - Soetjipto, Budi Eko; Wardana, Ludi Wishnu; Haribowo, Siget Fitrianto (Jurnal Ilmu Manajemen, 2025)
Employee performance is crucial to organizational success and is influenced by various determinants, including incentives and workload. This study presents a Systematic Literature Review (SLR) to examine the relationship between incentives, workload, and employee performance. The review synthesizes findings from previous studies to identify key trends, theoretical frameworks, and empirical evidence regarding how incentives motivate employees and how workload affects their productivity and well-being. Additionally, this study explores whether incentives can mitigate the negative impact of workload on performance. Using the PRISMA framework, research published between 2020 and 2025 was identified from databases such as Scopus. The findings highlight the dual role of incentives in enhancing motivation and job satisfaction while addressing the challenges posed by excessive workload. Therefore, Indonesian enterprises must build the appropriate incentive plan and manage workload optimally to establish a productive and healthy work environment. Long-term improvements in worker welfare and more optimal employee performance will come from the combination of well-balanced incentives and effective workload management. This study also identifies gaps in the existing literature and recommends future research directions to develop a more comprehensive understanding of these relationships.